Determinan Ketergantungan Impor Beras di Indonesia [Determinants of Rice Import Dependency in Indonesia] - Sahrul Paipan; Muhammad Abrar (Pusat Penelitian, Badan Keahlian DPR RI, 2020)
Rice is the staple food for most Indonesian people, but the government tends to import rice to meet their excess demand. This study aims to analyze the determinants of rice import dependence in the Indonesia period 1992-2017. ECM Model is applied to reveal the effects between independent variables on rice imports short-term and the long-term. Secondary data is sourced from the World Bank, FAO, and BPS. The research results show that in the long run the rice production does not influence rice imports, but it is significant and positive in the short term. Rice consumption, rupiah appreciation, foreign exchange reserves, and domestic rice prices influence rice imports positively and significantly in the long and short term. Meanwhile, GDP influences rice imports negatively and relative prices do not significantly influence rice imports in the long run and also short run. Imports of rice are caused by the lack of maximum rice absorption by The Indonesian Logistic Bureau (Bulog) and increasing rice consumption. The government should absorb the surplus of farmer’s rice by establishing direct cooperation between the government and farmers. The community can support the food diversification policy with various food and nutritious food.Keywords: rice, import, consumption, production, ECMAbstrakBeras merupakan kebutuhan pokok utama bagi penduduk Indonesia, namun pemerintah cenderung mencukupi kelebihan kebutuhan permintaan beras dengan impor. Penelitian ini bertujuan untuk menganalisis determinan ketergantungan impor beras di Indonesia periode tahun 1992-2017. Model ECM digunakan untuk menjawab tujuan tersebut, baik melihat pengaruhnya dalam jangka pendek maupun jangka panjang antara variabel bebas terhadap impor beras. Data sekunder bersumber dari World Bank, FAO dan BPS. Hasil penelitian menunjukkan dalam jangka panjang produksi beras tidak memengaruhi impor beras, namun dalam jangka pendek menjadi signifikan dan positif. Konsumsi beras, apresiasi rupiah, cadangan devisa, dan harga beras domestik berhubungan positif dan signifikan memengaruhi impor beras dalam jangka panjang maupun jangka pendek. Di sisi lain, PDB memengaruhi impor beras dan harga relatif tidak signifikan memengaruhi impor beras, baik dalam jangka jangka pendek maupun panjang. Impor beras terjadi disebabkan karena kurang maksimal Bulog menyerap beras petani dan meningkatnya konsumsi beras. Pemerintah diharapkan mampu menyerap surplus beras yang dimiliki petani dengan menjalin kerja sama langsung. Sementara itu, masyarakat juga diharapkan mendukung kebijakan diversifikasi pangan dengan mengkonsumsi aneka ragam pangan dan pangan bergizi.Kata kunci: beras impor, konsumsi, produksi, ECM